EXPERIENCES OF PARENTS HAVING CHILDREN WITH CHRONIC KIDNEY DISEASES: A QUALITATIVE STUDY IN PESHAWAR, KHYBER PAKHTUNKHWA - Muhammad Nadeem; Dr. Najma Naz; Irfan Ullah Khattak; Nasreen Ghani (International Journal of Contemporary Issues in Social Sciences, 2023)
Chronic Kidney Disease is main problem of concern worldwide. Millions of children are affected with Chronic Kidney Disease every year. The disease not only affects the health of the children but it is also associated with a variety of complications among the parents. Parents of children with chronic kidney disease experience social, psychological and mental health issues. To explore the experiences of parents having children with chronic kidney diseases. A qualitative study was carried out in Institute of Kidney diseases Peshawar to highlight the experiences of parents of children with chronic kidney diseases. Data were collected from overall 13 participants using semi structure guide. All required approvals from university, hospital and consents were granted from the participants before collection of the data. A total of 13 participants were included in the study. Overall, 98 open codes were identified in the study. After axial coding and thematic analysis, a total of 16 categories were contributed to four themes such as Care Burden, Intense Grief, Psychological Distress and Adaptation Barriers. The findings of the study concluded that the parents of children with Chronic Kidney Diseases experience in mental health issues. The parents bear excessive care burden and facing difficulties in coping with the problems.